Impact of gender on left atrial low-voltage zones in patients with persistent atrial fibrillation: results of a voltage-guided ablation - Marzak, Halim; Ringele, Romain; Matsushita, Kensuke; Marchandot, Benjamin; Fitouchi, Simon; Cardi, Thomas; Kanso, Mohamad; Schatz, Alexandre; Hammann, Justine; Ohlmann, Patrick; Morel, Olivier; Jesel, Laurence (Frontiers in Cardiovascular Medicine, 2023)
Background Gender-related differences have been reported in atrial fibrotic remodeling and prognosis of atrial fibrillation (AF) patients after ablation. We assessed in persistent AF the regional distribution of left atrial (LA) bipolar voltage and the extent of low-voltage zones (LVZ) according to gender as well as the results of a voltage-guided substrate ablation. Methods Consecutive patients who underwent a voltage-guided AF ablation were enrolled. LA endocardial voltage maps were obtained using a 3D electro-anatomical mapping system in sinus rhythm. LVZ was defined as <0.5 mV. Results A total of 115 patients were enrolled (74 men, 41 women). The LA bipolar voltage amplitude was twice lower in the whole LA (p < 0.01) and in each atrial region in women compared with men, whereas the LA indexed volume was similar. LVZ were found in 56.1% of women and 16.2% of men (p < 0.01). LVZ were also more extensive in women (p = 0.01), especially in the anterior LA. Atrial voltage alteration occurred earlier in women than in men. In a multivariate analysis, the female sex (OR 12.99; 95% CI, 3.23–51.63, p = 0.0001) and LA indexed volume (OR 1.09; 95% CI, 1.04–1.16, p = 0.001) were predictive of LVZ. Atrial arrhythmia-free survival was similar in men and women 36 months after a single ablation procedure. Conclusion The study reports a strong relationship between the female gender and atrial substrate remodeling. The female gender was significantly associated with higher incidence, earlier occurrence, and greater extent of LVZ compared with men. Despite the female-specific characteristics in atrial remodeling, LVZ-guided ablation may improve the AF ablation outcome in women.